2021
DOI: 10.1097/01.aoa.0000796268.93440.ad
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesiology Airway-related Medicolegal Cases From the Canadian Medical Protection Association

Abstract: F ET. O 2 ) of ≥ 90% is recommended. Preoxygenation is typically carried out using a tight-fitting facemask with 100% inspired oxygen fraction (FiO 2 ) at a flow rate of 10 L/ min, with 3 to 5 minutes of tidal breathing. As obstetrical intubation often requires prompt induction, alternative preoxygenation methods are being explored.A recent study used high-flow nasal oxygen for preoxygenation for term pregnant women. The study had an up-down sequential allocation design, so the predetermined number of VC breat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Airway related issues are most common and one should never get compromised while managing airway especially working in a periphery set up. 5 4. Recordkeeping in Anesthesia and Critical Care 6,7 Various invasive and risky procedures are carried out by the anesthesiologists in day to day life.…”
Section: Ethical Practicementioning
confidence: 99%
“…Airway related issues are most common and one should never get compromised while managing airway especially working in a periphery set up. 5 4. Recordkeeping in Anesthesia and Critical Care 6,7 Various invasive and risky procedures are carried out by the anesthesiologists in day to day life.…”
Section: Ethical Practicementioning
confidence: 99%
“…As minor airway events are relatively common, and if not managed appropriately may be a harbinger for more serious airway events, then major airway events may occur in any elective surgical patient. Elective patients, most of whom were not anticipated to have airway management difficulty, comprised 57% and 63% in recent studies of airway-related medicolegal closed-claims in Canada and the USA respectively [4,5]. Medicolegal claims represent the 'sharp end' of patient outcomes, with most patients involved having suffered brain damage or death directly related to their airway event(s).…”
Section: Consequencesmentioning
confidence: 99%
“…Understanding current clinical practice, and associated patient outcomes, informs quality improvement initiatives. From national audit projects [4, 6, 13], review of system‐specific databases [5, 14], to case report collections [15], observational studies can provide both overall patient care themes as well as powerful narratives of patient experiences [5, 6]. Recently, we have also seen international COVID‐19‐related prospective observational studies regarding both healthcare professional and patient risks [16, 17].…”
Section: Covid‐19mentioning
confidence: 99%
See 1 more Smart Citation
“…caused by difficult airway [2]. Crosby et al reviewed the 406 anesthesia-related civil litigation cases recorded by the Canadian Medical Protection Association from 2007 to 2016, and concluded that 11% of the disputes were caused by failure of airway management [3]. e incidence of difficult airway is different in different literature.…”
Section: Introductionmentioning
confidence: 99%